Dušikov oksid II: biološki učinki in učinkovine, ki sproščajo NO - Mravljak, Janez (Farmacevtski vestnik, 2005)
Nitric oxide, as a key mediator in many physiological and pathophysiological processes, expresses most of its biological effects by activation of soluble guanylyl cyclase. In some illnesses it is therapeutically desirable to increase its concentration, in others to inhibit its excessive formation. Appart from organic nitrates that have been used in therapy for several years, new NO donors with different mechanisms of dissociation and selective effects in other target effector systems and tissues have more recently been tested.
Keywords: biokemija; dušikov oksid